Cardiovascular, respiratory and metabolic responses to apnea induced by atlanto‐occipital intrathecal lidocaine injection in anesthetized horses. (5th February 2016) - Guedes, Alonso; Aleman, Monica; Davis, Eric; Tearney, Caitlin
Abstract: Objective: To determine physiologic responses to apnea‐induced severe hypoxemia in anesthetized horses. Study design: Prospective experimental study. Animals: Six university‐owned horses with a median (range) body weight of 500 (220–510) kg and aged 13.5 (0.8–24.0) years scheduled for euthanasia. Methods: Xylazine–midazolam–ketamine‐anesthetized horses breathing room air spontaneously were instrumented with a facial artery catheter for pressure measurement and blood sampling, and were made apneic with atlanto‐occipital intrathecal lidocaine (4 mg kg −1 ). Cardiopulmonary, biochemical and hematologic variables were recorded before (baseline) and every minute for 10 minutes after lidocaine injection. Results: PaO2 values were: baseline, 55 mmHg (7.3 kPa); 1 minute, 28 mmHg (3.8 kPa); 2 minutes, 18 mmHg (2.4 kPa); 3 minutes, 15 mmHg (2.0 kPa), and 4–10 minutes, (8–11 mmHg (1.1–1.5 kPa). PaCO2 values were: baseline, 50 mmHg (6.7 kPa); 1 minute, 61 mmHg (8.1 kPa), and 2–10 minutes, 64–66 mmHg (8.5–8.8 kPa). Base excess values at baseline, 1 minute and 2–10 minutes were 5.3 mmol L −1, 6.5 mmol L −1 and 7.0–8.1 mmol L −1, respectively. Pulse rates at baseline, 1 minute and 2–7 minutes were 36, 53 and 54–85 beats minute −1, respectively. Asystole occurred at 8 minutes. Pulse pressures were 50 mmHg at baseline and 1 minute, and 39 mmHg, 31 mmHg, 22 mmHg, 17 mmHg and 1–9 mmHg at 2, 3, 4, 5 and 6–10 minutes, respectively. Lactate was 0.9 mmol L −1 at baseline, progressively increasing to 1.7–2.4 mmol L −1 at 7–10 minutes. Packed cell volume increased after 7 minutes of apnea. There were no other major changes. Conclusions and clinical relevance: Apnea immediately exacerbated hypoxemia and hypercapnia and rapidly caused hemodynamic instability. Apnea in hypoxemic anesthetized horses is associated with a serious risk for progress to cardiovascular collapse.